PROTECTION OF ELECTRICAL COMPONENTS IN SOLAR ENERGY SHADE STRUCTURE - DEBARTOLO, Jack, III; BOSCAMP, Robert; HEADLEY, Thomas; NOTHUM, Michael, Jr (2018)
In accordance with various exemplary embodiments, solar energy shade structures and support systems are disclosed that have electrical components concealed or screened within columns located under the structure. For example, a solar energy structure may comprise: a solar panel support structure, a plurality of solar panels supported by the solar panel support structure, a plurality of vertical supports connected to the solar panel support structure for supporting the solar panel support structure elevated above a surface, and a column, located under the solar panel support structure. The column comprises an electrical component mounted to the column in a screened manner, wherein the electrical component comprises at least one of a string inverter, a combiner, and a battery. Selon divers modes de réalisation donnés à titre d'exemple, l'invention concerne des structures de store à énergie solaire et des systèmes de support qui comportent des composants électriques cachés ou masqués à l'intérieur de colonnes situées sous la structure. Par exemple, une structure à énergie solaire peut comprendre : une structure de support de panneau solaire, une pluralité de panneaux solaires supportés par la structure de support de panneau solaire, une pluralité de supports verticaux reliés à la structure de support de panneau solaire pour supporter la structure de support de panneau solaire élevée au-dessus d'une surface, et une colonne, située sous la structure de support de panneau solaire. La colonne comprend un composant électrique monté sur la colonne de manière masquée, le composant électrique comprenant un onduleur de branche, un combinateur et/ou une batterie.